Strong migratory connectivity across meta-populations of sympatric North Atlantic seabirds - Merkel, Benjamin; Descamps, Sebastien; Yoccoz, Nigel; Grémillet, David; Fauchald, Per; Danielsen, Jóhannis; Daunt, Francis; Erikstad, Kjell E.; Ezhov, Aleksey V.; Harris, Mike P.; Gavrilo, Maria; Lorentsen, Svein-Håkon; et al. (Marine Ecology Progress Series, 2021)
Identifying drivers of population trends in migratory species is difficult, as they can face many stressors while moving through different areas and environments during the annual cycle. To understand the potential of migrants to adjust to perturbations, it is critical to study the connection of different areas used by different populations during the annual cycle (i.e. migratory connectivity). Using a large-scale tracking data set of 662 individual seabirds from 2 sympatric auk meta-populations (common guillemots Uria aalge and Brünnich’s guillemots U. lomvia) breeding in 12 colonies throughout the Northeast Atlantic, we estimated migratory connectivity in seasonal space use as well as occupied environmental niches. We found strong migratory connectivity, within and between species. This was apparent through a combination of seasonal space use and occupied environmental niches. Brünnich’s guillemot populations grouped into 2 and common guillemot populations into 5 previously undescribed spatiotemporal clusters. Common guillemot populations clustered in accordance with the variable population trends exhibited by the species, while Brünnich’s guillemot populations are declining everywhere where known within the study area. Individuals from different breeding populations in both species were clustered in their space and environmental use, utilising only a fraction of the potential species-wide range. Further, space use varied among seasons, emphasising the variable constraints faced by both species during the different stages of their annual cycle. Our study highlights that considering spatiotemporal dynamics, not only in space but also in occupied environmental niches, improves our understanding of migratory connectivity and thus population vulnerability in the context of global change. Environmental niche · Inter-population mixing · Large-scale spatiotemporal dynamics · Light-level geolocation · Murres · Population spread · Seasonality